Penerapan PERMA No.1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan Agama Badung dalam Pencabutan Perkara Cerai Talak - I Gede Satya Bala Putra Dewa; I Nyoman Putu Budiartha; A.A Sagung Laksmi Dewi (Jurnal Analogi Hukum, 2019)
Rules of the Supreme Court or PERMA is basically a form of regulation which contains provisions of a legal nature of the event. In relation to rule on divorce, I need to know the difference between a PERMA No.1 Year 2016 with PERMA No.1 Year 2008 about mediation. namely, regarding the time limit shorter again 10 days earlier than the deadline for mediation 40 days now becomes 30 days in the count when the existence of the assignment orders for mediation. Both the parties are required to attend the mediation meeting immediately on the use of "or not by the power of the law of exception there is a reason that is considered legitimate for not attending meetings of the mediation, such as the State of being is not good or in conditions sick so it is not possible to present proven by affidavits from hospitals or doctors, or with a pedestal that concerned far outside his residence or country or are there is a task of the country, the demands of the profession or work which could not be left. This study aims to find out the procedure for the resolution of litigated divorce and application Perma No.1 Year 2016 in Badung Religious Courts. The type of research used in this study i.e. Empirical legal research that is taken from the fact that occur in the field, are obtained through the explanations of the informant and in learned with attitude is a real law or in accordance with the a fact of life in the community. The results of this study, namely, 1) that divorce litigation settlement procedure in the courts of badung religion as well as the procedure of settlement of the matter in the courts of other religious peerceraian that is equally subject to Islamic laws as well as any the applicable legislation. 2) Application Perma number 1 year 2016 in Badung Religious Courts have started to effectively. This can be seen in the report of the mediation of the year 2017 in the case with the number 0096/Pdt.G/2017/PA. Bdg. But in other words time mediation in court conditional nature of badung Religious meaning depending on the agreement of the parties in the mediation process. Then it can be inferred that any religious courts in an area with other areas are equally subject to Islamic law and all applicable laws and regulations, as well as the application of Perma No.1 Year 2016 regarding mediation can It is said that its application depends by nature are conditional meaning depending on the agreement of the parties in the mediation process. Peraturan Mahkamah Agung atau PERMA pada dasarnya adalah bentuk peraturan yang berisi ketentuan bersifat hukum acara. Dalam kaitannya dengan aturan mengenai perceraian,perlu diketahui perbedaan antara PERMA No.1 Tahun 2016 dengan PERMA No.1 Tahun 2008 tentang Mediasi, yakni mengenai batas waktu lebih singkat lagi 10 hari dibandingkan yang sebelumnya batas waktu untuk mediasi 40 hari sekarang menjadi 30hari di hitung saat adanya penetapan perintah untuk mediasi. Kedua para pihak diwajibkan untuk hadir langsung dalam pertemuan mediasi di dampingi atau tidak dengan kuasa hukum terkecuali ada suatu alasan yang dianggap sah untuk tidak menghadiri pertemuan mediasi, contohnya keadaan sedang tidak baik ataupun dalam kondisi sakit sehingga tidak mungkin untuk hadir dibuktikan dengan surat keterangan dari rumah sakit ataupun dokter pengampu, atau dengan alasan bahwa yang bersangkutan tinggal atau kediamannya jauh diluar negeri atau sedang ada tugas Negara, tuntutan dari profesi ataupun pekerjaan yang tidak bisa ditinggal. Studi ini bertujuan untuk mengetahui prosedur penyelesaian perkara cerai dan penerapan Perma No.1 Tahun 2016 di Pengadilan Agama Badung. Tipe penelitian yang digunakan dalam penelitian ini yaitu Penelitian Hukum Empiris yaitu diambil dari fakta yang terjadi di lapangan, yang di dapatkan melalui penjelasan-penjelasan dari informan dan di pelajari dengan sikap hukum yang nyata atau sesuai dengan kenyataan hidup di masyarakat. Hasil dari penelitian ini yaitu, 1) bahwa prosedur penyelesaian perkara perceraian di pengadilan agama badung sama halnya dengan prosedur penyelesaian perkara peerceraian di pengadilan agama lainnya yaitu sama-sama tunduk terhadap hukum islam serta segala peraturan perundang-undangan yang berlaku. 2) Penerapan Perma Nomor 1 tahun 2016 di Pengadilan Agama Badung sudah mulai efektif. Ini dapat dilihat pada laporan mediasi tahun 2017 dalam perkara dengan Nomor 0096/Pdt.G/2017/PA.Bdg. Akan tetapi Dengan kata lain waktu mediasi di Pengadilan Agama badung sifatnya kondisional artinya tergantung kesepakatan para pihak dalam proses mediasi. Maka dapat disimpulkan bahwa setiap pengadilan agama yang ada pada suatu daerah dengan daerah lainnya sama-sama tunduk terhadap hukum Islam dan segala peraturan perundang-undangan yang berlaku, serta penerapan Perma No.1 Tahun 2016 mengenai mediasi dapat dikatakan bahwa penerapannya tergantung dengan sifatnya yang kondisional artinya tergantung kesepakatan para pihak dalam proses mediasi.